2016
DOI: 10.5511/plantbiotechnology.16.0905a
|View full text |Cite
|
Sign up to set email alerts
|

A MYB-related transcription factor affects nodule formation in <i>Lotus japonicus</i>

Abstract: The MYB family is one of the largest groups of transcription factors in plants. Our previous microarray data revealed that a MYB-related gene (Ljmybr) was induced upon nodule formation in Lotus japonicus. As shown using real-time PCR, the expression of the Ljmybr in L. japonicus was up-regulated after M. loti infection. To determine the role of Ljmybr in the nodulation process, we created transgenic hairy roots in L. japonicus and then performed Ljmybr overexpression (MYBOX) or RNAi-mediated suppression (MYBRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…A starting point to find an answer should be the study of the relatively few signalling elements reported intervening in flowering, and other circadian-controlled processes, which would be worthwhile being evaluated in relation to biotic and abiotic stresses, i.e. , the putative PHYTOCHROME INTERACTING FACTOR4 ( Lj PIF4, Ono et al, 2010 ) Ljmybr , an MYB-related gene ( Duangkhet et al, 2016 ), clock-associated F-box proteins ( Boycheva et al, 2015 ), NOOT-BOP-COCH-LIKE (NBCL) regulators ( Magne et al, 2018 ) and the flowering regulation gene ( Lj2g3v1989150 , Shah et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…A starting point to find an answer should be the study of the relatively few signalling elements reported intervening in flowering, and other circadian-controlled processes, which would be worthwhile being evaluated in relation to biotic and abiotic stresses, i.e. , the putative PHYTOCHROME INTERACTING FACTOR4 ( Lj PIF4, Ono et al, 2010 ) Ljmybr , an MYB-related gene ( Duangkhet et al, 2016 ), clock-associated F-box proteins ( Boycheva et al, 2015 ), NOOT-BOP-COCH-LIKE (NBCL) regulators ( Magne et al, 2018 ) and the flowering regulation gene ( Lj2g3v1989150 , Shah et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%